Performance evaluation and human talent retention of workers in a construction and road maintenance company Cusco - 2022 - Valverde Guzman, Keila Fiorela (2025)
The objective of the study was to analyze the relationship between performance evaluation and human talent retention in workers of a construction and road maintenance company in Cusco - 2022. For this purpose, a quantitative methodology was used, with a correlational and applied approach and a non-experimental design. The population consisted of 135 workers, selecting a probability sample of 100 employees. Data collection was carried out by means of surveys, and the analysis of the information was performed through descriptive and inferential techniques. Eighteen items were used to measure the variable "performance evaluation", while 24 items were used for "talent retention". The validation of the instrument was carried out by means of expert judgment, and reliability was evaluated through Cronbach's alpha coefficient. The results showed a Spearman's Rho correlation coefficient of 0.711 between both variables, indicating a strong positive association. It is concluded that there is a significant and very strong relationship between performance evaluation and human talent retention, showing that an improvement in performance evaluation is directly linked to higher retention of key talent in the company. This finding highlights the importance of implementing effective performance evaluation systems to ensure the retention of valuable personnel in the organization.